Scientific and theoretical foundations in formation of the national self-consciousness of future teachers in the system of higher education of the Republic of Kazakhstan - Natalya Khan, Venera Sarbasova,; Tarantey, Viktor; Aliyeva, Dinara (Opción, 2019)
The study aims to investigate scientific and theoretical foundations in formation of the national self-consciousness of future teachers in the system of higher education of the republic of Kazakhstan via comparative qualitative research methods. As a result, the mastery of practical skills in the main activities (transformative, cognitive, value-orientation, communicative) ensures the formation of the behavioral component of the national self-consciousness. In conclusion, the effectiveness in the formation of the national self-consciousness is determined by the introduction into the educational process of a scientifically-based pedagogical model in the formation of the national self-consciousness and a set of interrelated pedagogical conditions.